Complementary Effect of Blending on the Volatile Composition of Albariño and Loureira White Wines (Vitis vinifera L.) from NW Spain - Vilanova, M.; Freire, L. (South African Journal of Enology and Viticulture, 2017)
Albariño and Loureira are very valuables white cultivars from NW Iberian Peninsula (NW Spain and North Portugal). The purpose of the study was to know how blending affects the volatile composition of Albariño and Loureira white wines. Four Vitis vinifera white wines (Albariño, Loureira, Caiño Blanco and Godello) were blended at different proportions resulting in four wines, two two-wine blends (83:17 Albariño-Caiño Blanco and 50:50 Loureira-Caiño Blanco) and two three-wine blends (48:32:20 Albariño-Loureira-Caiño Blanco and 35:35:30 Loureira-Caiño Blanco-Godello). The blended wines were compared with Albariño and Loureira single-wines. Volatile composition of wines was evaluated by GC-MS to show the changes in aroma compounds of the blends respect to varietal Albariño and Loureira wines. The highest concentration of total volatiles was shown for Loureira and Albariño single-wines. However, blended wines, especially with Loureira, showed an increase of terpenes and C13-norisoprenoids concentration. Discriminant analysis (DA) showed C6-alcohols and phenol volatiles as the variables that most contributed to the differentiation between Albariño and blended wines, whereas terpenes and C13-norisoprenoids were those that contributed to the differentiation Loureira vs blended. To show the sensory influence of volatiles Odour Activity Value (OAV) was calculated, showing the superiority of Loureira single-wines aroma and 50:50 LO-CB blended wines vs Albariño and the other blended wines. The blended wines with high proportion of Loureira supposed wines richer in volatile compounds and increased of complexity aromatic of the wines.